Characterization of adhesive bonded lap joints of C/C-SiC composite and Ti-6Al-4V alloy under varying conditions - Srivastava V.K. (My University, 2025)
Characterization of adhesive bonded lap joints of C/C-SiC composite and Ti-6Al-4V alloy under varying conditions were examined. The effect of glueline thickness, length, etching time, temperature, exposure time and strain rate were studied after adhesive bonding. The surface morphology was characterized by the scanning electron microscope. Results showed that the C/C-SiC adherence was sensitive to strain rate and temperature than the Ti-6Al-4V adherence, due to poor oxidizing resistance and high brittleness.